New Era of Studying RNA Secondary Structure and Its Influence on Gene Regulation in Plants - Yang, Xiaofei; Yang, Minglei; Deng, Hongjing; Ding, Yiliang (Frontiers in Plant Science, 2018)
The dynamic structure of RNA plays a central role in the post-transcriptional regulation of gene expression such as RNA maturation, degradation and translation. With the rise of the next-generation sequencing, the study of RNA structure has been transformed from in vitro low-throughput RNA structure probing methods to in vivo high-throughput RNA structure profiling. The development of these methods provides incremental studies on the function of RNA structure, revealing new insights of novel regulatory mechanisms of RNA structure in plants. The genome-wide scale RNA structure profiling allows us to investigate the general RNA structural features over tens of thousands of mRNAs and compare RNA structuromes between plant species. Here, we provide a comprehensive and up-to-date overview of the RNA structure probing methods, the latest discoveries on biological functions of RNA structure, genome-wide RNA structural features corresponding to their new regulatory mechanisms, and RNA structurome evolution in plants.